Scattering efficiency of a cloudy apple juice: Effect of particles characteristics and serum composition - Benitez, Elisa Ines (2007)
The effect of particles and serum characteristics on turbidity of natural, or "regular", and modeled cloudy apple juices was studied in this work. Modeled apple juices were made by re-dispersing a determined quantity of apple particles in a simplified serum (mainly glucose, hydrolyzed pectin, and malic acid in water). Only glucose was found to have a significant effect on turbidity. Particle size was affected by soluble solids concentration, which was attributed to conformational changes in juice particles aggregates, simultaneously with a reduction in particle solvatation. Scattering efficiency was determined in natural and modeled cloudy apple juice both experimentally from a nephelometric method, Qav*, and theoretically with the Mie theory, QMie. Decrease in juice specific turbidity at increasing soluble solids concentrations (X), was governed by the decrease of Qav* at increasing refractive index of the liquid medium nm. As predicted by theory, the scattering efficiency increased at increasing particle size, for a constant nm. Finally, calculated values of Qav* and QMie followed a power law relationship when correlated. This non-linear behavior was explained by considering that QMie is the theoretical scattering efficiency of monodisperse-homogeneous spheres, while Qav* is the experimental nephelometric scattering efficiency of polydisperse-irregular particles. © 2007 Elsevier Ltd. All rights reserved.